Arbuscular mycorrhizae increase biomass and nutrient uptake of tomato fertilized with struvite compared to monoammonium phosphate - Di Tomassi, Isako; Chatterjee, Neha; Barrios-Masias, Felipe H.; Zhou, Qiuhong; Gu, Chunhao; Margenot, Andrew J. (Plant and soil, 2021)
Purpose Struvite is a wastewater-derived P mineral that offers a means to redirect wastestream P flows to agroecosystems. The low water solubility of struvite (< 3%) has been reported to limit early-season crop P uptake. Arbuscular mycorrhizae (AM) could enhance dissolution of struvite and thereby increase crop utilization of struvite-P. We tested the hypothesis that AM would increase struvite dissolution and thereby enhance plant P uptake and biomass in a P-deficient soil. Methods We employed a tomato ( Solanum lycopersicum L.) genotype model with a wild-type mycorrhizal tomato (MYC) and a reduced mycorrhizal mutant ( rmc ). Monoammonium phosphate (MAP) was used as a highly water soluble P fertilizer for comparison with struvite. Results Struvite granules underwent 4-fold less dissolution (% mass remaining) than MAP granules, and apparent struvite dissolution was similar under MYC and rmc . However, scanning electron microscopy revealed qualitative differences in surface morphology of residual struvite between MYC and rmc . Under struvite fertilization, biomass of MYC was 22% greater than rmc, and P and N shoot uptake (mg plant −1 ) were 32% and 34% greater than rmc . Shoot biomass was 24% greater for MYC fertilized with struvite than with MAP, and shoot P and N uptake were 26% and 34% greater, respectively. Conclusion Increased N and P uptake by AM-associated tomato plants fertilized with struvite suggests AM as a strategy to surmount solubility constraints to the use of struvite as a fertilizer.